Modern Notions of Accent-ism: Findings, Conceptualizations, and Implications for Interventions and Research on Nonnative Accents. (January 2020) - Roessel, Janin; Schoel, Christiane; Stahlberg, Dagmar
Nonnative-accented speakers face prevalent discrimination. The assumption that people freely express negative sentiments toward nonnative speakers has also guided common research methods. However, recent studies did not consistently find downgrading, so that prejudice against nonnative accents might even be questioned at first sight. The present theoretical article will bridge these contradictory findings in three ways: (a) We illustrate that nonnative speakers with foreign accents frequently may not be downgraded in commonly used first-impression and employment scenario paradigms. It appears that relatively controlled responding may be influenced by norms and motivations to respond without prejudice, whereas negative biases emerge in spontaneous responding. (b) We present an integrative view based on knowledge on modern forms of prejudice to develop modern notions of accent-ism, which allow for predictions when accent biases are (not) likely to surface. (c) We conclude with implications for interventions and a tailored research agenda.